Caving method selection and evaluation Diavik A21 case study - Jakubec, J; Nakou, D; Kottmeier, C; Tang, M; Lewis, P; Sovka, J (MassMin 2024: Proceedings of the 9th International Conference & Exhibition on Mass Mining, 2024)
The Diavik Diamond Mine started open pit production in 2003. By 2005, underground development had commenced with plans to mine the A154 and A418 pipes. Several mining methods were evaluated and the sub-level retreat method was chosen for the A154S and A418 pipes, and blasthole stoping with cemented rockfill was chosen for the A154N pipe. In 2020, the A21 kimberlite pipe had advanced its open cast mining to the stage where an underground mining method had to be selected. Both the Sublevel Retreat (SLR) and Incline Caving (IC) mining methods were considered for the A21 pipe. The focus of this paper is to document the experience of underground mining at the Diavik Diamond Mine, the evaluation of the SLR and IC mining methods for the A21 pipe, and the final selection of a mining method for the development of the A21 underground mine.